USING PERFORMANCE MODELING TO DESIGN LARGE-SCALE SYSTEMS. - Barker, Kevin J.; Davis, Kei; Hoisie, Adolfy; Kerbyson, Darren J.; Lang, Michael; Pakin, Scott; Sancho, José Carlos (Computer (00189162), 2009)
The article focuses on the use of computer performance modeling to design ultrascale systems from start to actual use. It is stated that the method offers analytical formulas that describe the performance of an application running on a current supercomputer and that it supports prediction, insight and interpretation. Performance modeling has also reportedly been used to quantify systems before implementing optimization and can be integrated into a system's everyday operation.